1975
DOI: 10.1063/1.88430
|View full text |Cite
|
Sign up to set email alerts
|

X-ray topographic study of dark-spot defects in GaAs-Ga1−xAlxAs double-heterostructure wafers

Abstract: Dark-spot defects (DSD) in a GaAs-Ga1−xAlxAs double-heterostructure (DH) wafer are studied by x-ray topography. Such DSD’s are one of the primary sources of the dark-line defects (DLD) that cause rapid degradation of GaAs-Ga1−xAlxAs DH lasers. By using x-ray topography almost all DSD’s observed by photoluminescence topography are correlated with dislocations in a GaAs substrate. In addition, it is observed that some dislocations in the substrate are not sources of DSD’s when the dislocation axes are nearly par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…By analogy with GaAs (6) and InP (7) diodes, the electrical characteristics of CdTe p-n junctions should also depend on the dislocation density. Finally, from the studies of LPE growth on GaP (8), GaAs (9), and InP (10) substrates, the defect density of epitaxial layers is directly correlated with that of the substrate. The defect density of CdTe crystals is thus an important parameter for device applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with GaAs (6) and InP (7) diodes, the electrical characteristics of CdTe p-n junctions should also depend on the dislocation density. Finally, from the studies of LPE growth on GaP (8), GaAs (9), and InP (10) substrates, the defect density of epitaxial layers is directly correlated with that of the substrate. The defect density of CdTe crystals is thus an important parameter for device applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intrinsic gettering (IG) in CZ silicon wafers has been noticed to suppress surface microdefects which are harmful to IC devices such as bipolar and MOS (1-7). Moreover, it has been reported that the IG effect can be enhanced using two-step annealing before device processing (6)(7)(8)(9). In order to utilize IG effectively, it is important to examine the thermal properties and behavior of inner defects and then to evaluate the effectiveness of IG in wafers taken from various portions of seed to tail of a crystal ingot in connection with the establishment of critical annealing conditions to achieve IG effectively.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of rapid degradation are: (1) the optical output decreases rapidly during constant current operations (or, in the case of constant output power operations, there is either a rapid increase in the operating current or a rapid decrease in the internal quantum efficiency) and ( 2) non-emitting regions are formed within the emitting region (the active region). There are three types of non-emitting regions: i) dark-line defects (DLDs), 9) ii) dark-spot defects (DSDs), 10) and iii) dark regions. 11) Here, the half-life of a component (the time taken for its output to drop to half its initial level) is less than 100 hours at room temperature.…”
Section: Outline Of the Three Degradation Modes Of Semiconductor Opti...mentioning
confidence: 99%
“…8 (a The characteristics of rapid degradation are: 1) the optical output decreases rapidly during constant current operations (or, in the case of constant output power operations, there is either a rapid increase in the operating current or a rapid decrease in the internal quantum efficiency) and 2) non-emitting regions are formed within the emitting region (the active region). There are three types of non-emitting regions: i) dark-line defects (DLDs) (23), ii) dark-spot defects (DSDs) (24), and iii) dark regions (25). Here, the halflife of a component (the time taken for its output to drop to half its initial level) is less than 100 hours at room temperature.…”
Section: Device Degradationmentioning
confidence: 99%